Recent Development-1 of CADTEL Software: The Resolution and Focusing Parameters Affecting at the Properties of Electron Magnetic Lenses - Hasan, Hussain S.; Obaid, Sura Allawi; Erhayief, Muhssen Salbookh (Iraqi Journal of Science, 2022)
Computer Aided Designing Tools of Electron Lenses (CADTEL) is a software packages cares about design, compute and plot simultaneously of the objective and projector properties of electron magnetic lenses. The developments in CADTEL software leads to contain a large fields and methods, adding to previous publish in 2013. The current improvement is inserting of some important parameters which are the resolution and focusing parameters. These parameters are angular semi-angle (α), focusing power (β), resolution limit (δ), image rotation (θ), spherical aberration (Cs), defocus (ΔZ), wave aberration (Χwab), depth of field (Dfld), and depth of focus (Dfoc) at certain magnification conditions. Thus, user can easily compute and plot, according to relations and forms, the effect of these parameters at the lens properties of four magnification conditions; zero, infinite and finite (low and high) magnification modes. This work introduces a new development for CADTEL software which is an interactive visual interface in electromagnetic lenses.Whereas, it reflects a substantial reduction of time and resources desired for training new users and researchers in electron optics field. The results and curves representations appear with visual interfaces which are coded in visual basic programing language. In addition, the computations and figures which were plotted appeared that complete identification between these results which are obtained from CADTEL and that from other software’s and direct computations methods.